Fried, Ed., Socialism In America - From The Shakers Tot He Their International - A Documentary History - Poindexter, John (Teaching History: A Journal of Methods, 1993)
When, in 1970, Doubleday published Socialism in America, the editor wrote in his preface, "There is no anthology of this kind now available." Although over two decades have passed since its initial appearance and the literature on American Socialism has proliferated, his earlier claim "still holds true: this is still the only available anthology on the subject." Its reissuance is a welcome readdition to the study of American Socialism. Fried’s collection provides the student access to many documents that otherwise would be unavailable except in their original publication.